Kontribusi Konsep Diri Siswa dan Keterlibatan Orangtua terhadap Pemilihan Sekolah Lanjutan di SMPN 25 Padang - Cipta, Aswidy Wijaya; Marjohan, Marjohan; Daharnis, Daharnis (Universitas Negeri Padang, 2014)
Each year students will look for a suitable school for students. Problems arise when there are a lot of options that provide diverse schools offer to prospective students. Contributions of students self concept and parents involvement supposed to influence in the selection of secondary schools. This study aimed to describe: 1) self-concept of students of SMPN 25 Padang, 2) parents involvement of SMPN 25 Padang, 3) students secondary school selection, 4) the contribution of students self-concept against secondary school selection, 5) contribution parental involvement against secondary school selection, 6) the contribution of students self-concept and parental involvement against secondary school selection. This corelational descriptive research applied quantitative method. The population of the research were students in grade IX of SMPN 25 Padang also using proportional random sampling technique. The instrument of this research was the Likert scale model. The data obtained were analyzed by using descriptive statistic, simple regression and multiple regression. The research findings were: 1) students self concept in average were in high category, 2) parental involvement in average were in high category, 3) students selection of secondary school were in high category, 4) there are significance different between students self concept against students selection of secondary school amount 44.3% (R = 0.666), 5) there are significance different between parental involvement toward students selection of secondary school amount 51.1% (R = 0.715), and 6) there are significance different between students self concept and parental involvement toward students selection of secondary school amount 54.2% (R = 0.736). The implication of this research may useful to design a guidance and counseling program, especially career guidance.